Optimizing the evaluation model of green building management based on the concept of urban ecology and environment - Lyu, Chengxi; Hu, Jiaxi; Zhang, Rui; Chen, Wang; Xu, Pengpeng (Frontiers in Ecology and Evolution, 2023)
Eco-city and green building are the global development strategies in the world today. In order to improve the management level of green buildings in the process of urbanization, based on the theory of urban ecology, a reciprocal symbiosis evaluation index model is proposed. On this basis, the collaborative relationship model between eco city and green building is established, and the green building management framework based on the collaborative theory is constructed. Through the expert survey method to determine the evaluation indicators used, and analyze the relationship between various subsystems of the city. Then, the analytic hierarchy process is used to build a three-level evaluation index system including the target layer, the criterion layer and the index layer. The weight of the evaluation index system is calculated by the combination of the chromatography method and the entropy weight method, and a scientific evaluation index system is established. The gray comprehensive evaluation method is used to evaluate the construction of the green building management system. On the basis of the index system, the analytic hierarchy process is used to calculate different weight coefficients, which makes the evaluation model easy to use and lays a foundation for subsequent research.